2021
DOI: 10.1007/s12325-021-01796-6
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab Plus Tremelimumab in Solid Tumors: A Systematic Review

Abstract: Introduction: Cancer immunotherapy represents one of the most important innovations in modern medicine. Durvalumab is an anti-programmed cell death ligand 1 (PDL-1) agent which is currently under investigation in several studies in combination with the anti-cytotoxic T lymphocyte-associated protein 4 (CTLA-4) drug tremelimumab. The aim of this review was to systematically identify and revise the current scientific literature investigating the combination of these two drugs in solid tumors. Methods: A digital s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 95 publications
(131 reference statements)
0
12
0
Order By: Relevance
“…The study also found no differences in treatment-related AEs between the two groups. In addition, a systematic review by Arru et al 16 focused on treatment efficacy and did not provide detailed data on AEs; therefore, data on AEs in DT-only regimens are required to establish the risks and benefits of DT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The study also found no differences in treatment-related AEs between the two groups. In addition, a systematic review by Arru et al 16 focused on treatment efficacy and did not provide detailed data on AEs; therefore, data on AEs in DT-only regimens are required to establish the risks and benefits of DT therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Tremelimumab locates at the B7-1/2 binding site of CTLA-4, allowing CTLA-4 to bind more tightly to Tremelimumab. Therefore, Tremelimumab blocks the action of CTLA-4 in cancer by binding more closely to CTLA-4 than B7-1/2 [5] and ultimately achieving the purpose of treating cancer. The current study results showed that the use of Tremelimumab alone to treat tumors showed lower overall anti-tumor activity, which may be due to the different modes of Tremelimumab and traditional CTLA-4 antibodies.…”
Section: Mechanism Of Action Of Tremelimumab In Cancer Therapymentioning
confidence: 99%
“…Along with ipilimumab, another anti-CTLA-4 antibody known as tremelimumab has entered clinical trials, but its antineoplastic activity was low while it was administered as a single drug, and it has also shown substantial side effects (the incidence of thyroid disorders is 0-5.2%). However, its association with durvalumab for treating mesothelioma, melanoma, NSCLC, gastroesophageal or colorectal tumors could be promising, even though some studies have not shown a substantial benefit added by tremelimumab compared to durvalumab alone (50)(51)(52). A phase 3 clinical trial (CheckMate 037) has shown that anti-PD-1 antibodies have both higher efficacy and a superior safety profile compared to ipilimumab (53).…”
Section: Fda-approved Immune Checkpoint Inhibitorsmentioning
confidence: 99%